FRI0257 A Retrospective Database Analysis Describing Recurrent Infection Risk among Patients Using Tnf-Inhibitors, Other Biologic DMARDS and Non-Biologic Dmards. (10th June 2014) - Accortt, N.A.; Bonafede, M.; Collier, D.; Iles, J.; Anthony, M.; Curtis, J.R.
Abstract : Background: Patients with inflammatory rheumatic conditions and psoriasis are often treated with immunosuppressive medications that can increase risk for infections but relatively little research has focused on the risk of recurrent infections with these agents. Objectives: To compare the incidence of recurrent serious infections (RSI) among patients taking TNF inhibitors (TNFi), other biologic DMARDs (OB), and non-biologics DMARDs (NB). Methods: Patients with rheumatic conditions (rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS)) or psoriasis (PsO) with a serious infection (defined by hospitalization or outpatient visit with IV antibiotic use), between 1/1/2006 and 12/31/2011 were identified in the Truven Health MarketScan Commercial and Medicare Supplemental Databases. Index date was defined as the date of hospital discharge or end of IV antibiotic use for an infection diagnosis. Patients were required to be continuously enrolled for 12 months prior to the index date and to have at least one claim for a TNFi, OB or NB during the pre-index year. Follow up time for identification of RSIs began 61 days after the latter of hospitalization discharge or end of IV antibiotic use. Patients were followed for up to 18 months. The primary outcome was RSI during the follow-up period, defined as an infection diagnosis on 1) two non-diagnostic outpatient claims between 2 and 30 days apart plus a claim for IV antibiotic administration or 2) an inpatient claim. Incidence rates (IR) per 100 patient-years (PY) with 95% confidence intervals (CI) were calculated. Results: 26, 840 patients met inclusion criteria; 42% used a TNFi, 2.8% used an OB, and 55.2% used a NB in the year prior to the index infection. Mean age was 61.1 (SD=14.0) and 71.6% were female. The average length of follow-up was 376 days (SD=179). The majority of patients had RA (85.8%), followed by PsO (17.2%), PsA (13.4%) and AS (4.5%). The rate of RSI was lowest among patients with pre-index TNFi use 21.0/100 PY (95% CI: 20.2, 21.8), followed by patients using NB (23.4/100 PY, 95% CI: 22.6, 24.1) and patients using OB agents (28.2/100 PY, 95% CI: 24.3-32.0). RSI rates were higher for patients over age 60 (25.0/100 PY, 95% CI: 24.2-25.8) than those under age 60 (19.6/100 PY, 95% CI: 18.8-20.3). RSI rates appeared modestly lower for patients with post-index TNFi use (16.9/100PY, 95% CI: 16.1-17.7) compared to patients with post-index methotrexate use (19.0/100PY, 95% CI: 18.2-19.7). Among TNFi users, RSI risk was greater for patients treated with a concomitant corticosteroid (19.2/100 PY, 95% CI: 18.2-20.3) than those without (12.5/100PY, 95% CI: 11.4-13.7); the same was true for methotrexate users (21.1/100PY vs. 14.3/100PY, respectively). RSI rates appeared similar within the most commonly used TNFi post-index (etanercept: 16.1/100 PY, 95% CI: 15.0-17.2; adalimumab: 15.2/100 PY, 95% CI: 13.9-16.5; infliximab: 18.1/100 PY, 95% CI: 16.4-19.9). Conclusions: Rates of recurrent serious infections were lowest among patients treated with TNF inhibitors compared to patients treated with other biologic agents or non-biologic DMARDs. Acknowledgements: Study funded by Immunex, a wholly owned subsidiary of Amgen Inc. Disclosure of Interest: N. Accortt Shareholder of: Amgen, Employee of: Amgen, M. Bonafede: None declared, D. Collier Shareholder of: Amgen, Employee of: Amgen, J. Iles Shareholder of: Amgen, Employee of: Amgen, M. Anthony Shareholder of: Amgen, Employee of: Amgen, J. Curtis Grant/research support: Amgen, Abbvie, BMS, Celgene, Centocor, CORRONA, Crescendo, Genentech, Janssen, Pfizer, Roche, UCB, Consultant for: Amgen, Abbvie, BMS, Celgene, Centocor, CORRONA, Crescendo, Genentech, Janssen, Pfizer, Roche, UCB DOI: 10.1136/annrheumdis-2014-eular.3771